1999
DOI: 10.1055/s-1999-3632
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Deoxyglycopyranosyl Thioureas from Glycals

Abstract: The reaction of glycals with phenylselenenyl chloride followed by treatment with KNCS lead to 2-deoxy-2-phenylselenoglycopyranosyl isotiocyanates which were further transformed into 2-deoxyglycopyranosyl thioureas.Sugar isothiocyanates are versatile synthetic intermediates in carbohydrate chemistry. By exploiting the strong electrophilic character of the NCS group, a wide variety of other functional groups can be accessed which, in turn, may be subjected to other transformations. The synthesis, chemistry and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…By using the basic reaction, (1-6), (1-1)-thiourea-linked oligosaccharides, thiourea-bridged glycodendrimers, multiple thiourea binding receptors have been prepared (Fig. 1) [28,[93][94][95][96][97][98][99][100][101][102][103].…”
Section: Application As Sensormentioning
confidence: 99%
“…By using the basic reaction, (1-6), (1-1)-thiourea-linked oligosaccharides, thiourea-bridged glycodendrimers, multiple thiourea binding receptors have been prepared (Fig. 1) [28,[93][94][95][96][97][98][99][100][101][102][103].…”
Section: Application As Sensormentioning
confidence: 99%
“…For example, the electrophilic addition of halogens to cyclic enol ethers has been investigated early by Lemieux and Fraser-Reid who proposed a general mechanism involving the initial formation of carbenium ions which, upon nucleophilic attack by halide ion, give mainly the products of thermodynamic control. Later on, it has been shown that the product formation is under kinetic control and that the stereoselectivity depends on the solvent polarity, the structure of the enol ether, and the nature of the halogen .…”
Section: Introductionmentioning
confidence: 99%